(untitled) (Czech Journal of International Relations, 2009)
Daniel Joyner (ed.): Non-Proliferation Export Controls: Origins, Challenges, and Proposals for Strengthening. 1st ed. Burlington: Ashgate Publishing Company, 2006, 243 stran, ISBN 978-0-7546-4460-6.